Komunikasi Kebijakan Pemerintah terhadap Daya Saing Komoditas Bawang Merah di Kabupaten Majalengka - Lola Rahmadona; Anna Fariyanti; Burhanuddin Burhanuddin (Jurnal Komunikasi Pembangunan, 2017)
Shallot is one of commodities having high value, so that many farmers are cultivating it but Indonesia still remains as net importer of shallot. The objective of this study is to analyze the communication of government policies towards competitiveness on shallot commodity in the district of Majalengka. The data have been analyzed by the method of the Policy Analysis Matrix (PAM) to determine the level of profit and competitiveness, as well as the impact of the policy. A total of 37 farmers were selected as respondents by using purposive sampling technique. The result showed that shallot farming in the district of Majalengka was financially profitable but economically unprofitable. The analysis of the competitiveness showed the shallot farming in the district of Majalengka had no competitiveness. The government policy provides protection against the price of shallot. Meanwhile, the government policy towards the input is still a disincentive to farmers. Shallot farmers have to pay more expensive input than they should be. But simultaneously, the government policy on input and output is still supportive for shallot production in the country. Dialogical communication process with the bottom up approach can encourage the successful of implementation of policies to improve the competitiveness of shallot in the district of Majalengka.